2014
DOI: 10.1111/jbi.12445
|View full text |Cite
|
Sign up to set email alerts
|

Bergmann meets Scholander: geographical variation in body size and insulation in the koala is related to climate

Abstract: Aim Body size often varies clinally, with dominant explanations centred on how body size influences heat exchange (e.g. Bergmann's rule). However, for endotherms, pelage properties can also dramatically alter heat exchange – a point emphasized by Scholander in the 1950s but which has received little attention in biogeographical analyses. Here, we investigate how geographical variation in both body size and fur properties of the koala (Phascolarctos cinereus) is related to climate. Location Eastern Australia. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 56 publications
2
41
0
Order By: Relevance
“…The four shallow genetic lineages identified here do not correspond to previously described sub-species, and it is now apparent that morphological variation within the koala represents a cline reflecting gradients in environmental conditions across the distribution [12,16]. In a previous phylogeographic study, Houlden et al [18] found a similar pattern of genetic divergence, noting the presence of ‘three clusters’ in their phylogenetic analyses, which correspond to three of the four identified in the present study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The four shallow genetic lineages identified here do not correspond to previously described sub-species, and it is now apparent that morphological variation within the koala represents a cline reflecting gradients in environmental conditions across the distribution [12,16]. In a previous phylogeographic study, Houlden et al [18] found a similar pattern of genetic divergence, noting the presence of ‘three clusters’ in their phylogenetic analyses, which correspond to three of the four identified in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…size and colouration; [12,1416]). Initially, three koala subspecies were recognised on the basis of variation in size and colouration: P .…”
Section: Introductionmentioning
confidence: 99%
“…In both birds and mammals, adaptive body size-independent changes to BMR and thermal conductance, in combination with additional behavioral and physiological traits, allow species to occur in a wide range of thermal environments. Although we focus on interspecific comparisons, similar physiological and morphological changes likely play a role in within-species adaptation to local environments (25).…”
Section: Discussionmentioning
confidence: 99%
“…Birds use a suite of behaviours and physiological mechanisms to control heat exchange and thus reduce the energy required for thermoregulation. This can include use of micro refugia, postural changes including ptiloerection of feathers, and modification of peripheral blood flow [29,30,48,52,55,56,63,64]. Such strategies are used in both winter and summer and can be effective at maintaining body mass in the face of challenging conditions [65].…”
Section: Differences Between the Speciesmentioning
confidence: 99%
“…In cool climates, winter rainfall can reduce the insulation capacity of fur and feathers, thereby increasing heat loss and leading to reductions in body condition [27][28][29]. Winter rain may also indirectly increase the costs of thermoregulation by negatively affecting the availability of food [27].…”
Section: Introductionmentioning
confidence: 99%